Time Harmonic Elastography Reveals Sensitivity of Liver Stiffness to Water Ingestion - Ipek-Ugay, Selcan; Tzschaetzsch, Heiko; Hudert, Christian; Garcia, Stephan Rodrigo Marticorena; Fischer, Thomas; Braun, Juergen; Althoff, Christian; Sack, Ingolf (Ultrasound in Medicine and Biology, 2016)
The aim of the study was to test the sensitivity of liver stiffness (LS) measured by time harmonic elastography in large tissue windows to water uptake and post-prandial effects. Each subject gave written informed consent to participate in this institutional review board-approved prospective study. LS was measured by time harmonic elastography in 10 healthy volunteers pre- and post-prandially, as well as before, directly after and 2 h after drinking water. The LS–time function during water intake was measured in 14 scans over 3 h in five volunteers. LS increased by 10% (p = 0.0015) post-prandially and by 11% (p = 0.0024) after pure water ingestion, and decreased to normal values after 2 h. LS was lower after overnight fasting than after 2-h fasting (3%, p = 0.04). Over the time course, LS increased to post-water peak values 15 min after drinking 0.25 L water and remained unaffected by further ingestion of water. In conclusion, our study indicates that LS measured by time harmonic elastography represents an effective-medium property sensitive to physiologic changes in vascular load of the liver.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Blood volume; Hepatic vasculature; Liver stiffness; Prandial effects; Time harmonic elastography; Water uptake